Patient-reported outcomes for US oncology labeling: review and discussion of score interpretation and analysis methods. (2nd November 2015) - Shields, Alan; Coon, Cheryl; Hao, Yanni; Krohe, Meaghan; Yaworsky, Andrew; Mazar, Iyar; Foley, Catherine; Globe, Denise
Abstract : This paper describes ways to approach the conceptual and practical challenges associated with interpreting the clinical meaning of scores produced by patient reported outcome (PRO) questionnaires, particularly when used to inform efficacy decisions for regulatory approval for oncology products. Score interpretation estimates are not inherent to PRO questionnaires per se, instead, vary dependent upon sample and study design characteristics. Scores from PRO measures can be interpreted at the individual and group level, and each carries its own set of statistics for evaluating differences. Oncology researchers have a variety of methods and data analytic strategies available to support their score interpretation needs, which should be considered in the context of their a priori knowledge of the target patient population, the hypothesized effects of treatment, the study design and assessment schedule, and the inferences and decisions to be made from the PRO data.